Ответ:
1) 3a^2 b^2 +ab(8a^2 b-b^2) =ab(3ab+8a^2 b-b^2) =ab×b(3a+8a^2 - b) =ab^2 (3a+8a^2 - b)
2) 3a^2 b^2 +ab((2a^2 b)^3)^2 =ab(3ab+((2a^2 b)^3)^2) =ab(3ab+(2a^2 b)^6)=ab(3ab+64a^12 b^6)=abab(3+64a^11 b^5)=a^2 b^2 (3+64a^11 b^5)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
3^2b^2 + 8a^3b^2 - ab^3. Итого:
2 * 2 * 3 * 2 * 1 * 3 = 72.
Во втором:
2a^12 b^6. 6 * 12 = 72.
Ответ:
1) 3a^2 b^2 +ab(8a^2 b-b^2) =ab(3ab+8a^2 b-b^2) =ab×b(3a+8a^2 - b) =ab^2 (3a+8a^2 - b)
2) 3a^2 b^2 +ab((2a^2 b)^3)^2 =ab(3ab+((2a^2 b)^3)^2) =ab(3ab+(2a^2 b)^6)=ab(3ab+64a^12 b^6)=abab(3+64a^11 b^5)=a^2 b^2 (3+64a^11 b^5)